Study of the impact of nuclease Cas9 delivery methods on knockout efficiency in T lymphocytes using the CRISPR /Cas9 genome editing system in the experimental T cell line model Jurkat - Pokladok, Kathrine S.; Meleshko, Alexander N.; Kisel, Maryia S. (Experimental Biology and Biotechnology, 2026)
The development of allogeneic CAR-T cells represents a promising direction in cancer immunotherapy, overcoming the limitations of autologous approaches. One of the key steps in creating such cells is the efficient delivery of CRISPR/Cas9 genome editing components into them. This article explores strategies for optimising electroporation parameters for nuclease Cas9 (mRNA, plasmid vector, protein) to enhance genome editing efficiency. The optimised protocol may contribute to the standardisation of allogeneic CAR-T cell manufacturing, improving their therapeutic efficacy and safety.